Minimalistic strategy for coronary sinus lead implant: A single tool capable of electrophysiological mapping, pressure measurement, and angiography. Issue 10 (13th August 2020) - Samanta, Rahul; Ng, Ben; Ha, Andrew; Bhaskaran, Abhishek; Bokhari, Mahmoud; Nair, Krishnakumar; Nanthakumar, Kumaraswamy
Abstract: Background: Left ventricular (LV) lead implantation for cardiac resynchronization therapy (CRT) may be confounded by contrast load during attempted cannulation and lead dislodgement during guiding catheter splitting. An LV lead implant system with a steerable single catheter that completely avoids the use of guiding catheters when needed, acquires atrioventricular electrograms, measures intracardiac pressures, permits CS angiography, and has the ability to direct a coronary angioplasty wire that will lead the final delivery of LV lead into a CS tributary, may help limit contrast use and avoid lead dislodgement at CS guide sheath removal. Methods and Results: In this article as a proof of concept, we describe the use of this minimalist technique as a first line approach in six patients who had standard indications for CRT. The LV lead was successfully implanted in a target vein in all patients without acute complications. Contrast was not used in half the group and the LV lead was successfully implanted without guiding catheter in four patients. The implantation technique evolved through the series and in the final patient, no guiding sheath or contrast was used. Postimplant lead positions on chest X‐ray and lead parameters were stable in all patients at follow‐up. Conclusion: In proof of concept paper, we describe a technique of LV lead implantation potentially without the use of contrast and standard CS guiding catheters. Once familiar, this approach may provide a less complicated strategy.